Effect of Temperature on Sporophore Development and Extracellular Enzyme Production in Agaricus Bitorquis (Quel.) Saccardo - Lee, Su Wee (2001)
This study was carried out to determine the optimum temperature of different stages of Agaricus bitorquis fruit body development from 2 mm to cup stage. Changes in extracellular CM-cellulase and laccase in compost during growth and fruiting were monitored in order to understand the underlying biochemical changes. Fruit bodies were produced at all sets of temperature conditions in rhythmic cycle. Effect of temperature on sporophore development and enzyme production could only be truly tested in the first flush as non-uniform condition of substrate occurred in the later flushes. Incubation of 2 to 10 mm stage at 23°C (Sets II, III) gave an increase of 58.9% in percentage of primordia survival when compared to that at 30°C (Set I). Exposure of 10 mm stage sporophores to 30°C did not affect them from growing satisfuctorily. Maximum yield (g of fresh mushroom weight) was attained by Set III cultures, followed by Set II cultures and Set I cultures. The highest average weight of harvested mushroom was attained by cultures kept at 30°C throughout 2 mm to cup stage (Set I). The time taken for sporophores maturation was shortest in Set I, Set II, and Set III temperature condition, in descending order. A rise in temperature from 23°C to 30°C during 10 mm to cup stage speeded up the sporophore maturation process but resulted in smaller mushroom. The production of CM-cellulase and laccase activities was closely associated with the mycelial growth, fruit bodies initiation and their subsequent development to full maturity. Laccase activity increased with mycelial growth, peaked at maximum growth and then declined rapidly at the onset of fruiting. The activity remained low during fruit body development period but increased suddenly during the flush interval. CM-cellulase activity showed the reverse pattern by remaining low throughout mycelial growth but an increase at the onset of fruiting. The activity remained high during fruit body development and declined rapidly during flush interval. Effect of temperature on the enzymes production was significant only during the 2 to 10 mm stage but not during the subsequent 10 mm to cup stage. The results revealed the extra-sensitivity of young sporophores to environmental factors during the 2 to 10 mm stage.